2013
DOI: 10.1159/000348667
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weight Loss and Exercise on Apelin Serum Concentrations and Adipose Tissue Expression in Human Obesity

Abstract: Objective: Apelin is an adipokine which plays a role in the regulation of glucose homeostasis and may contribute to the link between increased adipose tissue mass and obesity related metabolic diseases. Here we investigate the role of omental and subcutaneous (SC) adipose tissue apelin and its receptor APJ mRNA expression in human obesity and test the hypothesis that changes in circulating apelin are associated with reduced fat mass in three weight loss intervention studies. Methods: Apelin serum concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
80
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 59 publications
6
80
1
2
Order By: Relevance
“…Furthermore, there is a greater expression in white adipose tissue compared with the subcutaneous adipose tissue in accordance with the data of OLEFT rats [81,82]. Several research groups have found gender differences in serum vaspin.…”
Section: Vaspinsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, there is a greater expression in white adipose tissue compared with the subcutaneous adipose tissue in accordance with the data of OLEFT rats [81,82]. Several research groups have found gender differences in serum vaspin.…”
Section: Vaspinsupporting
confidence: 86%
“…Vaspin expression was also found in hypothalamus, stomach and pancreatic islets [82] but is not expressed in the subcutaneous tissue, brown adipose tissue and other not fat tissues.…”
Section: Vaspinmentioning
confidence: 93%
“…Apelin expression in adipose tissue is regulated by nutritional status. In obese subjects, APJ-apelin expression is increased and this up-regulation could be reversed after diet or surgery-induced weight loss [141] . Moreover, changes in insulin levels might be involved for both apelin and APJ regulations in adipose tissue, according to the severity of insulin resistance [140] .…”
Section: Apelinmentioning
confidence: 99%
“…The first report in humans of plasma apelin concentrations was shown in obese and hyperinsulinemic subjects [139,141] where plasma apelin levels are increased. In morbidly obese patients with or without diabetes, apelin levels were only higher in the diabetic morbidly obese subjects [151] .…”
Section: Apelinmentioning
confidence: 99%
“…Yapılan çalışmalar sonucunda apelinin biyolojik olarak en aktif formunun 13 aminoasitten oluşan apelin-13 olduğu ve etkilerini APJ reseptörüne bağlanarak ortaya koyduğu gösterilmiştir [20,21] mRNA'nın özellikle yüksek konsantrasyonda beyincik, damar endoteli, kalp, akciğer, böbrek ve prostat dokusunda olduğu belirlenmiştir [20,[22][23][24][25]. Hem apelininin hemde reseptörünün insan prostat dokusunda tespit edilmesi [25], vücutta artan yağ doku miktarı ile apelin sentezinin arttığının bilinmesi [26,27] ve kanser gelişiminde obezitenin bir risk faktörü olması [19,28], apelin ile prostat kanseri arasında bir ilişki olabileceğinin düşündürmektedir. Yapılan çalışmalarla apelinin anjiyojenezi, lenfanjiyogenezi ve tümör büyümesini uyardığı gösterilmiştir [29,30].…”
Section: Introductionunclassified